2007
DOI: 10.1002/cne.21446
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in the structure and innervation of follicle‐sinus complexes to an aquatic environment as seen in the Florida manatee (Trichechus manatus latirostris)

Abstract: Florida manatees are large-bodied aquatic herbivores that use large tactile vibrissae for several purposes. Facial vibrissae are used to forage in a turbid water environment, and the largest perioral vibrissae can also grasp and manipulate objects. Other vibrissae distributed over the entire postfacial body appear to function as a lateral line system. All manatee vibrissae emanate from densely innervated follicle-sinus complexes (FSCs) like those in other mammals, although proportionately larger commensurate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 70 publications
5
55
0
Order By: Relevance
“…This basic innervation pattern of the deep vibrissal nerve is similar to that described in previous studies [Waite and Li, 1993;Rice et al, 1997;Ebara et al, 2002]. A recent study has demonstrated the dual innervation of the deep vibrissal nerve in the Florida manatee [Sarko et al, 2007]; however, the deep vibrissal nerve innervation pattern was singular in the present study, not dual ( fig. 5 ).…”
Section: Innervation Of the Deep Vibrissal Nervesupporting
confidence: 34%
See 1 more Smart Citation
“…This basic innervation pattern of the deep vibrissal nerve is similar to that described in previous studies [Waite and Li, 1993;Rice et al, 1997;Ebara et al, 2002]. A recent study has demonstrated the dual innervation of the deep vibrissal nerve in the Florida manatee [Sarko et al, 2007]; however, the deep vibrissal nerve innervation pattern was singular in the present study, not dual ( fig. 5 ).…”
Section: Innervation Of the Deep Vibrissal Nervesupporting
confidence: 34%
“…Many studies have investigated the vibrissal FSC, and the results have been presented schematically [Fundin et al, 1999;Ebara et al, 2002], on electron micrographs [Sakita et al, 1994;Sarko et al, 2007], and using immunofluorescence analysis . Thus, the basic structure, innervation pattern, and distribution of blood vessels within the vibrissal FSC are known.…”
Section: Introductionmentioning
confidence: 99%
“…In another semi-aquatic mammal, the Australian water rat (Hydromys chrysogaster) , the number of myelinated nerve fibers in DVN is about the same as in otters . In the pinnipeds and sirenians that have been examined so far, the vibrissa system and its innervation is even more developed than in the studied semi-aquatic mammals [Yablokov and Klevezal, 1964;Ling, 1968Ling, , 1977Stephens et al, 1973;Hyvärinen and Katajisto, 1984;Hyvärinen, 1989Hyvärinen, , 1995Reep et al, 1998Reep et al, , 2001Reep et al, , 2002Marshall et al, 2006;Sarko et al, 2007]. In the bearded seal the number of mystacial vibrissae is greatest (about 244 mystacial vibrissae per seal) and the innervation of one F-SC is also slightly greater or about the same as in the ringed seal [Hyvärin- en and Katajisto, 1984;Marshall et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…In pinnipeds and sirenians the progressive development of the vibrissal system was possibly the most important adaptation of the sensory system to the aquatic environment [Stephens et al, 1973;Hyvärinen and Katajisto, 1984;Sokolov, 1986;Hyvärinen, 1989Hyvärinen, , 1995Dehnhardt and Kaminski, 1995;Dehnhardt et al, 1998Dehnhardt et al, , 2001Reep et al, 2001Reep et al, , 2002Marshall et al, 2006;Sarko et al, 2007]. Furthermore, in pinnipeds the vibrissae are used not only in tactile exploration but also in many social displays [Miller, 1975;Kastelein and van Gaalen, 1988;Dehnhardt and Kaminski, 1995].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation